The Analysis of Digital Competency for Student Teachers at Rajabhat University - Nuansri, Mesa; Pantuworakul, Kullachat (Journal of Humanities and Social Sciences Thonburi University, 2022)
This research aimed to: 1) analyze the current state of the digital competency of student teachers at Rajabhat University, and 2) compare the average scores of the digital competency of student teachers at Rajabhat University of different genders, majors, and GPA The samples were 900 student teachers at Rajabhat University. The data were collected by using a 5-point rating scale. Data were analyzed by descriptive statistics methods including frequency, percentage, means, standard deviation, as well as by inferential statistical methods including the independent samples t-test and F-test for one–way ANOVA. The research findings showed that: 1) The student teachers at Rajabhat University had the overall digital competency at a high level. When considering each factor separately, it was found that all factors were at a high level as well. 2) The student teachers at Rajabhat University had no difference in digital competency when considered by gender. However, the student teachers majoring in science had significantly higher digital competency than those majoring in social sciences. Also, the student teachers with high and intermediate grade point averages has a higher competency level than those with a lower grade point averages at a statistically significant level of 0.05.